Patients presenting with lower urinary tract symptoms who most deserve to be investigated for primary bladder neck obstruction - Nicolò Schifano (Nature Portfolio, 2021)
Abstract We aimed to investigate clinical features potentially useful in primary bladder neck obstruction (PBNO) diagnosis in men presenting with lower urinary tract symptoms (LUTS). Data from 1229 men presenting for LUTS as their primary complaint at a single centre were retrospectively analysed. All patients underwent a comprehensive medical and physical assessment, and completed the International Prostate Symptoms Score. All patients were investigated with uroflowmetry, and trans-rectal ultrasound imaging to define prostate volume. Urodynamic evaluation was performed when the diagnosis of benign prostatic enlargement was not confirmed and the patient presented a significant chance of detrusor overactivity or underactivity. As per our internal protocol, patients < 60 years old with bothersome LUTS and > 60 years with a prostate volume (PV) < 40 mL were also investigated with urethrocystoscopy to rule out urethral stricture. Logistic regression analysis tested clinical predictors of possible PBNO. Of 1229 patients, 136 (11%) featured a clinical profile which was consistent with PBNO. Overall, these patients were younger (p < 0.0001), had lower BMI (p < 0.0001), less comorbidities (p = 0.004) and lower PSA values (p < 0.0001), but worse IPSS scores (p = 0.01) and lower PV values (p < 0.0001) compared to patients with other-aetiology LUTS. At multivariable analysis, younger age (OR 0.90; p = 0.003) and higher IPSS scores (OR 1.12; p = 0.01) were more likely to be associated with this subset of patients, after accounting for other clinical variables. One out of ten young/middle-aged men presenting for LUTS may be affected from PBNO. Younger patients with more severe LUTS systematically deserve an extensive assessment to rule out PBNO, thus including urethrocystoscopy and urodynamics with voiding-cysto-urethrogram.